2022
DOI: 10.1002/jmv.27735
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characterization of SARS‐CoV‐2 variants of concern and mouse‐adapted strains in mice

Abstract: SARS‐CoV‐2 has evolved into a panel of variants of concern (VOCs) and constituted a sustained threat to global health. The wildtype (WT) SARS‐CoV‐2 isolates fail to infect mice, while the Beta variant, one of the VOCs, has acquired the capability to infect standard laboratory mice, raising a spreading risk of SARS‐CoV‐2 from humans to mice. However, the infectivity and pathogenicity of other VOCs in mice remain not fully understood. In this study, we systematically investigated the infectivity and pathogenicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…All mice ( n = 9 per strain) were infected with 10 5 50% tissue culture infective doses (TCID 50 ) of the Beta variant. Based on previous studies where the Beta variant was used to infect wild-type mice ( 14 16 ), we selected day 3 postinfection (p.i.) as the endpoint at which all animals were euthanized and lungs were collected to quantify the infectious virus titers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All mice ( n = 9 per strain) were infected with 10 5 50% tissue culture infective doses (TCID 50 ) of the Beta variant. Based on previous studies where the Beta variant was used to infect wild-type mice ( 14 16 ), we selected day 3 postinfection (p.i.) as the endpoint at which all animals were euthanized and lungs were collected to quantify the infectious virus titers.…”
Section: Resultsmentioning
confidence: 99%
“…In a pseudotype-based entry assay, the pseudoviruses carrying the Beta variant of the spike protein attached more efficiently to the mouse ACE2 receptor than the alpha variants, suggesting that the K417N and E484K mutations in the RBD of the Beta variant may further enhance the binding to the mouse receptor ( 11 ). Recently, a comparative infection study in BALB/c mice revealed that the Beta variant replicates more efficiently than the alpha or delta variant ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a pseudotype-based entry assay, the pseudoviruses carrying the beta variant spike attached more efficiently to the mouse ACE2 receptor than the alpha variants, suggesting that the K417N and E484K mutations in the RBD of beta variant may further enhance the binding to the mouse recptor (11). Recently, a comparative infection study in BALB/c mice revealed that the beta variant replicates more efficiently than the alpha and delta variant (15).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the N501Y mutation, the spike of the beta B.1.135 variant carries the K417N mutation that was previously reported in a virulent mouse-adapted SARS-CoV-2 variant (13). Several studies have shown the ability of the beta variant to replicate to some extent in WT mice species such as C57BL/6 (11, 12) and BALB/c (14, 15). Here, we wanted to explore whether the beta SARS-CoV-2 variant replicates more efficiently in severe combined immune deficient (SCID) mice than in the reported wild type mice and whether in such case, SCID mice can be used to develop a suficienlty robust infection model to study the efficacy of small molecules inhibitors of SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%